Pengaruh Guru PAK Sebagai Fasilitator Terhadap Motivasi Belajar Siswa Kelas VII SMP Negeri 3 Pakkat Kabupaten Humbang Hasundutan Tahun Pembelajaran 2023/2024 - Roma Uli Manullang; Tiurma Berasa; Limmarten Simatupang; Tianggur Medi Napitupulu; Dame Taruli Simamora (Jurnal Teologi Injili dan Pendidikan Agama, 2023)
The purpose of this study was to determine the existence of a positive and significant effect of PAK Teacher as a Facilitator on the learning motivation of seventh grade students of SMP Negeri 3 Pakkat Kab. Humbang Hasundutan Learning Year 2023/2024. The research method used is descriptive quantitative research method. The population was all seventh grade students of SMP Negeri 3 Pakkat as many as 54 people and the entire population was used as respondents in the study. Data were collected using a positive closed questionnaire of 34 items, namely 13 items for variable X and 21 items for variable Y. The results of data analysis show that there is a positive and significant influence of PAK teachers as facilitators on the learning motivation of seventh grade students of SMP N 3 Pakkat Kab. Humbang Hasundutan Learning year 2023/2024: 1) Analysis requirements test: a) positive relationship test obtained rxy = 0.529> rtable (=0.05, n=54)=0.226. b) significant relationship test obtained tcount = 4.497> ttable (=0.05, dk=n-2=52)=2.000. 2) Effect test: a) Regression equation test, obtained regression equation Y ̂="2" 9, "37"+0.88X. b) Regression determination coefficient test (r2) =28%. Thus Ha is accepted and H0 is rejected.